Dynamic flow treatment of Monoethanolamine (MEA) wastewater using activated carbon, chitosan and rice husk / Mohd Najib Razali, Noor Adilah Md Salehan and Nurul Asmawati Roslan - Razali, Mohd Najib; Md Salehan, Noor Adilah; Roslan, Nurul Asmawati (Universiti Teknologi MARA, Pulau Pinang, 2015)
This paper presents the performance of activated carbon, chitosan and rice husk in treating monoethanolamine (MEA) wastewater in order to evaluate the feasible method to recycle and reuse the MEA in the carbon dioxide (CO2)removal unit and at the same time maintaining the amine concentration. The adsorption performance of activated carbon was compared to the chitosan and rice husk. Adsorbent dosage and circulation time were varied in this experiment. MEA wastewater before and after the treatment were analyzed for residue oil and amine concentration. Amine contaminated wastewater contains about 2057 mg/L of residue oil and 65 % of amine concentration. The results showed that application of activated carbon managed to reduce the residue oil by up to 95 % and maintained the amine concentration with loss of 6 % at the defined optimum experimental condition (weight of adsorbent: 6 wt% , contact time: 8.5 h). For chitosan and rice husk, the results showed reduction of residue oil by up to 90 % and 71 % respectively. Meanwhile for amine concentration, both showed the same result as activated carbon which is 6 % loss at the same experiment conditions. In conclusion, activated carbon showed the best adsorption performance followed by chitosan and rice husk. Activated carbon showed the best performance as it has the highest surface area compared to chitosan and rice husk.